Improving the Capabilities of Micro, Small and Medium Enterprises in Financial Planning and Risk Management - Inayati Nuraini Dwiputri; Dwi Wulandari; Santi Merlinda; Vidya Purnamasari (Unram Journal of Community Service, 2025)
The existence of some micro business entrepreneurs who still do not understand well the principles of finance and business risk management, a community service activity is needed in this field. Knowledge of clear financial principles is needed in order to maintain business continuity and efforts to improve the business owned both in terms of turnover and profit to be obtained. There are still quite a lot of micro business entrepreneurs who do not know clearly about the strategy of managing business cash flow and managing risk mitigation that will be faced. This understanding is very important for micro business entrepreneurs to know. A good understanding of financial planning for micro business will be able to help micro business to maintain their business continuity. Therefore, this community service activity was made in an effort to provide solutions to the problems faced by micro business in Batu City, Indonesia in particular. Batu City was chosen as this community service activity because it is one of the tourist cities with high tourist visits in East Java and there are many MSME entrepreneurs in Batu City.